Synergistic effects of a combined salbutamol-nitroprusside regimen in acute myocardial infarction and severe left ventricular failure. Issue 6212 (16th February 1980) - Fowler, M B; Timmis, A D; Chamberlain, D A
Abstract : The haemodynamic effects of a simultaneous infusion of salbutamol and nitroprusside were measured in 20 patients with acute myocardial infarction and severe left ventricular failure. Six patients also had clinical manifestations of cardiogenic shock. Ten patients received salbutamol first with the subsequent addition of nitroprusside; in the other 10 patients nitroprusside was infused first. Salbutamol was infused at a constant rate of 20 micrograms/min in all patients, while the dose of nitroprusside, which averaged 51.25 micrograms/min, was adjusted to reduce left ventricular filling pressure (measured as pulmonary artery end-diastolic pressure) to approximately 15 mm Hg with reference to sternal angle. Cardiac index increased in all patients from a mean of 1.8 to 2.6 l/min/m2 while pulmonary artery end-diastolic pressure fell significantly from 24 to 16 mm Hg. The adverse effects were small in most patients: heart rate did not increase significantly and systolic arterial pressure fell on average from 112 to 96 mm Hg. Ten of the 20 patients survived to leave hospital. Nitroprusside accounted for most of the fall in filling pressure irrespective of treatment sequence, whereas both drugs contributed to the augmented cardiac output. The haemodynamic benefits of this combined regimen were considerably greater than those achieved by either drug alone. Thus salbutamol and nitroprusside have synergistic effects which influence favourably the two principal manifestations of left ventricular dysfunction after extensive myocardial infarction.